PENGEMBANGAN SUMUR PRODUKSI DAN INJEKSI DI LAHAN SAWAH PEKON AMBARAWA TIMUR, PRINGSEWU - Rustadi; Darmawan, I Gede Boy (Nemui Nyimah, 2024)
The development of shallow groundwater-based irrigation has been carried out by many farmers to meet water needs in sub-optimal land in Pekon Ambarawa Timur. Several wells have failed to obtain groundwater and others have decreased discharge which makes pumping costs uneconomic. Measurements across two 2D geoelectric trajectories have been made to obtain the presence of shallow aquifers. Data acquisition using the ARES instrument, Wenner Schlumberger configuration with a track length of 200 m and space between electrodes of 5 m. The results of sampling in two passes, the presence of aquifers formed lenses in the dominant environment of clay material at a depth of 2-30 m. In addition to being influenced by clay materials that are low permeable, there are also melts and intrusions forming some igneous rocks. To meet the purpose of irrigation sources, the manufacture of wells is placed in the presence of aquifer lenses. In addition to production, it can also be developed as an injection well-capturing puddles of rainwater filling shallow aquifers.